Association between serum pyridoxal 5′-phosphate levels and chronic obstructive pulmonary disease: findings based on NHANES 2005–2010 - Liu, Yanbin; Yan, Jun (Frontiers in Nutrition, 2025)
ObjectiveVitamin B6 is involved in regulating a variety of biological reactions in cell metabolism, and possesses antioxidant and anti-inflammatory biological functions. 5′-pyridoxal phosphate (PLP) is the main biologically active form of vitamin B6. There is currently no research on the correlation between serum PLP levels and chronic obstructive pulmonary disease (COPD) prevalence. This study aims to explore the relationship between serum PLP levels and COPD prevalence.MethodsThis cross-sectional study included adult participants with complete data on COPD diagnosis and serum PLP levels from 2005 to 2010 National Health and Nutrition Examination Survey (NHANES) database. Generalized linear model (GLM) was employed to analyze the association between serum PLP levels and COPD prevalence. The restricted cubic spline (RCS) curve and threshold effect analysis were used to explore the potential non-linear relationship between serum PLP levels and COPD prevalence. Subgroup analysis was carried out to assess the robustness of the relationship between serum PLP levels and COPD prevalence.ResultsA total of 11,103 participants were included in this study, of whom 830 were diagnosed with COPD. Higher PLP levels are associated with a reduced prevalence of COPD. GLM analysis confirmed that the groups with higher PLP levels (Q3 and Q4) had a significantly lower prevalence rate of COPD compared to the group of Q2. The RCS curves showed a non-linear “L”-shaped relationship between serum PLP levels and COPD prevalence. The threshold effect analysis found a critical point of 43.3 nmol/L. When serum PLP level is below 43.3 nmol/L, there is a negative correlation between serum PLP levels and COPD prevalence (p for overall <0.001, p for nonlinear <0.001). Subgroup analysis and interaction tests confirmed the robustness of the relationship.ConclusionThis study is the first to discover a non-linear relationship between serum PLP levels and COPD prevalence. Higher serum PLP levels are associated with a reduced prevalence of COPD.